Allergic Reactions at Enzyme Replacement Therapy in Children with Mucopolysaccharidosis Type II - Julia G. Levina; Nato D. Vashakmadze; Leyla S. Namazova-Baranova; Elena A. Vishneva; Natalia V. Zhurkova; Kamilla E. Efendieva; Anna A. Alekseeva; Vera G. Kalugina ("Paediatrician" Publishers LLC, 2021)
Mucopolysaccharidosis type II (MPS II; Hunter syndrome) is rare hereditary disease caused by changes in the IDS gene and associated deficiency of lysosomal enzyme iduronate-2-sulfatase (I2S). The main treatment scheme for children with MPS II is enzyme replacement therapy (ERT) with recombinant human I2S. The major issue of ERT is development of allergic (sometimes up to severe anaphylaxis) reactions to recombinant enzymes. The article covers features of infusion-related reactions to ERT, it describes pathogenesis, diagnostic criteria management algorithm of anaphylaxis. Whereas, there is the need of further studies on allergic infusion-related reactions to ERT in children.